3045 – A REPROGRAMMED THROMBOTIC PLATELET PHENOTYPE IN LIPOEDEMA AND LYMPHOEDEMA - Cameron, Scott; Aggarwal, Anu; Hamer, Annelise; Guntapalli, Suman; Aleman, Jose; Li, Xuefeng; Burton, Robert; Ademoyo, akirayii; Pascual, Crystal; Godwin, Matthew; Bartholomew, Jerry; Bhandari, Rohan (Experimental hematology, 2022)
Lipoedema exclusively affects women, manifesting with enhanced subcutaneous limb fat and is often mistaken for lymphoedema. Since both are inflammatory disorders, we hypothesized platelet hyperreactivity and thrombosis may occur. Thrombotic outcomes in patients treated for lymphedema (n=14,958) and lipo-lymphedema were examined, followed by blood from patients ex vivo for a platelet-mediated and non-platelet-mediated thrombotic phenotype. Activation of platelets by FACS (healthy, lymphoedema, lipoedema) and thrombosis in platelet-deplete plasma (thrombin and fibrin production by videomicroscopy) were determined. Nanostring technology interrogated the platelet transcriptome for biomarkers later validated in plasma by ELISA and ROC curve analysis. Platelet transcriptomics revealed elevated platelet factor 4 (PF4) in lymphoedema and lipoedema: plasma [PF4] discriminated lipoedema from lymphoedema from BMI-matched subjects (PF4 cut-point 472 ng/mL, AUC 0.74 [0.59-0.90], P=0.0015 vs. AUC 0.50[0.33-0.67], p=0.99, respectively). Increased platelet receptor activity was observed through PAR1 (lymphoedema 8975 MFI, lipodema 6604 MFI vs. 3015 MFI healthy, P< 0.001); thromboxane (lymphoedema 7884 MFI, lipoedema 5681 MFI vs. 2338 MFI healthy, P=0.002); P2Y12 (lymphoedema 2160 MFI, p=0.008, lipoedema 1175 MFI, p=NS vs. 960 MFI healthy). Fibrin generation was greater in lymphoedema vs. matched controls [n=25; 32949±1199 vs. n=21; 28037±1212 a.u., p=0.02] while thrombin generation was less in lipoedema [n=29; 357±18 vs. n=20; 413 ±15 AU/L p=0.03]. Lymphoedema and lipoedema have enhanced platelet reactivity and thrombosis through different mechanisms. Elevation of plasma PF4 in lipoedema may facilitate the diagnosis. Antiplatelet therapy should be considered in lymphoedema and lipoedema to avoid adverse thrombotic events.